Plany inwestycyjne gmin ze środków Unii Europejskiej (na przykładzie wybranych gmin powiatu radomszczańskiego) - Brzeziński, Cezary (The Communities' Investment Plans From the EU Funds (on the Example of Selected Communities in the Radomsko Local Government Administration), 2006)
Poland's accession to the EU in May 2004 enabled territorial self-government to use the means of Structural Funds. The legal basis of this participation is the National Development Plan for the years between 2004 and 2006 which will be realized among others by the multi-funded Integrated Regional Operational Programme (IROP) IROP's aim is to create the conditions for the increase of the regions' competitiveness and to prevent marginalization of some areas so as to promote long lasting economic development of the country, its economic social and territorial coherence and its integration with the EU. To determine the communities' investment plans from the EU funds the local development plans of 10 communities in the Radomsko poviat were analyzed. Assuming that the number and size of the projects filled is the reflection of the communities' needs it can be stated that the analyzed self-governments units feel the greatest needs for building and modernizing appliances for dumping and cleaning sewage, building and modernization of community and poviat roads and communal refuse economy. The propositions of investment presented describe the strategic problems of poviat development. Lots of problems that poviat copes with like e.g. bad condition of agriculture cannot be realized from IROP and with communities fund but with SOP "Restructuration and modernization of the food sector and rural development " and with the help of the Agency of the Development and Modernization of Agriculture and with the help of farmers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 705-714